A human-like bile acid pool induced by deletion of hepatic Cyp2c70 modulates effects of FXR activation in mice - de Boer, Jan Freark (J Lipid Res, 2020)
Bile acids (BAs) facilitate intestinal absorption of lipid-soluble nutrients and modulate various metabolic pathways through the farnesoid X receptor (FXR) and Takeda G-protein-coupled receptor 5. These receptors are targets for therapy in cholestatic and metabolic diseases. However, dissimilarities in BA metabolism between humans and mice complicate translation of preclinical data. Cytochrome P450 family 2 subfamily c polypeptide 70 (CYP2C70) was recently proposed to catalyze the formation of rodent-specific muricholic acids (MCAs). With CRISPR/Cas9-mediated somatic genome editing, we generated an acute hepatic Cyp2c70 knockout mouse model (Cyp2c70(ako)) to clarify the role of CYP2C70 in BA metabolism in vivo and evaluate whether its activity modulates effects of pharmacologic FXR activation on cholesterol homeostasis. In Cyp2c70(ako) mice, chenodeoxycholic acid (CDCA) increased at the expense of βMCA, resulting in a more hydrophobic human-like BA pool. Tracer studies demonstrated that, in vivo, CYP2C70 catalyzes the formation of βMCA primarily by sequential 6β-hydroxylation and C7-epimerization of CDCA, generating αMCA as an intermediate metabolite. Physiologically, the humanized BA composition in Cyp2c70(ako) mice blunted the stimulation of fecal cholesterol disposal in response to FXR activation compared with WT mice, predominantly due to reduced stimulation of transintestinal cholesterol excretion. Thus, deletion of hepatic Cyp2c70 in adult mice translates into a human-like BA pool composition and impacts the response to pharmacologic FXR activation. This Cyp2c70(ako) mouse model may be a useful tool for future studies of BA signaling and metabolism that informs human disease development and treatment.